2020
DOI: 10.1038/s41467-020-16128-5
|View full text |Cite
|
Sign up to set email alerts
|

Btk SH2-kinase interface is critical for allosteric kinase activation and its targeting inhibits B-cell neoplasms

Abstract: Bruton’s tyrosine kinase (Btk) is critical for B-cell maturation and activation. Btk loss-of-function mutations cause human X-linked agammaglobulinemia (XLA). In contrast, Btk signaling sustains growth of several B-cell neoplasms which may be treated with tyrosine kinase inhibitors (TKIs). Here, we uncovered the structural mechanism by which certain XLA mutations in the SH2 domain strongly perturb Btk activation. Using a combination of molecular dynamics (MD) simulations and small-angle X-ray scattering (SAXS)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 56 publications
4
20
0
Order By: Relevance
“…This initiates the formation of a signaling complex comprising further adapter proteins and providing docking sites for phosphatidylinositol (PI) 3-kinase and phospholipase Cγ2 (PLCγ2) [ 18 ]. PI3-kinase activation increases membrane levels of PI 3,4,5-trisphosphate (PIP3) that binds with high affinity to the PH-domain of Btk thereby leading to its translocation to the plasma membrane and complex conformational changes of the enzyme also involving the SH2 domain [ 22 , 23 ]. Lyn and Syk then phosphorylate Btk at Y-551 in the kinase domain, and subsequent autophosphorylation at Y-223 in the SH3 domain completes the activation of Btk [ 18 , 19 , 22 , 24 , 25 ] ( Figure 1 ).…”
Section: Role Of Btk In Platelet Signaling and Platelet Effects Ofmentioning
confidence: 99%
“…This initiates the formation of a signaling complex comprising further adapter proteins and providing docking sites for phosphatidylinositol (PI) 3-kinase and phospholipase Cγ2 (PLCγ2) [ 18 ]. PI3-kinase activation increases membrane levels of PI 3,4,5-trisphosphate (PIP3) that binds with high affinity to the PH-domain of Btk thereby leading to its translocation to the plasma membrane and complex conformational changes of the enzyme also involving the SH2 domain [ 22 , 23 ]. Lyn and Syk then phosphorylate Btk at Y-551 in the kinase domain, and subsequent autophosphorylation at Y-223 in the SH3 domain completes the activation of Btk [ 18 , 19 , 22 , 24 , 25 ] ( Figure 1 ).…”
Section: Role Of Btk In Platelet Signaling and Platelet Effects Ofmentioning
confidence: 99%
“…The SH2 domain and kinase domain together form an allosteric interface, which has been reported to be critical for the activation of BTK. Interestingly, Duarte et al [7] have recently demonstrated that this interface can contain SH2 mutations in XLA, which dramatically impacts BTK activation. The cysteine residue at position 481 of the kinase domain (C481) of BTK is a region of particular interest due to it being a target of many BTK inhibiting drugs.…”
Section: The Structure Of Btkmentioning
confidence: 99%
“…Small angle X-ray scattering (SAXS) data suggested quite early that BTK adopts an extended arrangement of its domains ( Márquez et al, 2003 ), however, the functional state that this extended conformational state reflects is unclear. More recent work has demonstrated that a BTK SH2 specific binding protein abrogates the kinase activity of BTK by blocking a predicted SH2/kinase domain interface required for activation ( Duarte et al, 2020 ; Jeong et al, 2020 ). The interface between SH2 and kinase domains in TEC family and other tyrosine kinases is known to play a critical role in enhancing kinase activity beyond the isolated kinase domain ( Nagar et al, 2003 ; Joseph et al, 2007 ; Filippakopoulos et al, 2008 ; Lamontanara et al, 2014 ).…”
Section: Sh3 and Sh2 Domains Influence The Kinase Domain Regulatory Apparatusmentioning
confidence: 99%